GENRENS ELASTISKE SPÆNDVIDDE: Indledende betragtninger - Sjørslev, Inger; Segal, Lotte Buch; Skrubbeltrang, Jørgen; Madsen, Mette My; Møhl, Perle (Tidsskriftet Antropologi, 2017)
Indledende betragtninger.